Blast off into space like Mae Jemison - Moss, Caroline, 1987- (Moss, Caroline, 1987- Work it, girl., 2020)
In this imaginatively illustrated book from the Work It, Girl series, discover how Mae Jemison became the first African American woman in space in this true story of her life. Then, learn 10 key lessons from her work you can apply to your own life. When Mae Jemison was a little girl, she loved science, dancing and dinosaurs. She watched the Apollo moon landings and wondered why none of the astronauts were women - and she just didn't buy the answers she was given.